Better Preparation and Training Determine Home Care Workers' Self-Efficacy in Contributing to Heart Failure Self-Care. (April 2023) - Stawnychy, Michael A.; Ringel, Joanna B.; Barbara Riegel,; Sterling, Madeline R.
Objective: Identify determinants of home care workers' (HCW) self-efficacy in contributing to heart failure (HF) self-care. Methods: Secondary analysis of a survey ( n = 328) examining characteristics of HCWs caring for adults with HF in New York. Self-efficacy assessed using Caregiver Self-Efficacy in Contributing to Self-Care Scale. Standardized scores range 0–100; ≥ 70 points indicate adequate self-efficacy. Characteristics determined by self-efficacy (low vs. adequate). Prevalence ratios with 95% confidence intervals (PR [95% CI]) were estimated using multivariable Poisson regression with robust standard errors. Results: Home care workers with adequate self-efficacy had at least some prior HF training (55% vs. 17%, p < .001) and greater job satisfaction (90% vs. 77%, p = .003). Significant determinants for adequate self-efficacy were employment length (1.02 [1.00–1.03], p = .027), preparation for caregiving (3.10 [2.42–3.96], p < .001), and HF training (1.48 [1.20–1.84], p < .001). Conclusion: Home care agencies and policy-makers can target caregiving preparation and HF training to improve HCWs' confidence in caring for adult HF patients.